ANALYSIS OF DENTURE BASE IMPACT ON THE DENTURE FOUNDATION AREA TISSUES - Kalashnikov, D.V.; Kindiy, D.D.; Korol, D.M.; Kindiy, V.D. (World of Medicine and Biology, 2020)
The article presents the results of the study of the dental base impact on the denture foundation area tissues. The study was conducted in 149 patients aged 41 to 74 years. Removable partial laminar dentures for the upper and lower jaws were made of plastics "Ftorax" and "Etacryl-02" by three technologies: in a "water bath", in a dry polymerizer under the pressure and in an advanced injection molding machine. The results obtained allow us to recommend the technology of manufacturing removable partial laminar dentures in the advanced injection molding machine for using in dental orthopedics clinic.